Diversity Drives Innovation: The Impact of Female-Driven Publications. (29th May 2022) - Smith, Rachel M; Rathore, Srishti; Donnelly, D'Andrea; Nicksic, Peter J; Poore, Samuel O; Dingle, Aaron M
Abstract: Background: Gender disparities are pervasive in academic plastic surgery. Previous research demonstrates articles authored by women receive fewer citations than those written by men, suggesting the presence of implicit gender bias. Objectives: The aim of this study was to describe current citation trends in plastic surgery literature and assess gender bias. The expectation was that women would be cited less frequently than their male peers. Methods: Articles published between 2017 and 2019 were collected from 8 representative plastic surgery journals stratified by impact factor. Names of primary and senior authors of the 50 most cited articles per year per journal were collected and author gender was determined via online database and internet search. The median numbers of citations by primary and senior author gender were compared by Kruskal-Wallis test. Results: Among 1167 articles, women wrote 27.3% as primary author and 18% as senior author. Women-authored articles were cited as often as those authored by men ( P  > 0.05) across all journal tiers. Articles with a female primary and male senior author had significantly more citations than articles with a male primary author ( P  = 0.038). Conclusions: No implicit gender bias was identified in citation trends, a finding unique to plastic surgery. Women primary authors are cited more often than male primary authors despite women comprising a small fraction of authorship overall. Additionally, variegated authorship pairings outperformed homogeneous ones. Therefore, increasing gender diversity within plastic surgery academia remains critical.